Modelling the Effect of Macro-economic Variables on Pension Contribution in Nigeria - , Abdulrahaman Bala Sani; , Idris Sani; , Adamu Hassan (Archives of Current Research International, 2022)
In recent years, the performance of pension contribution funds administrators in Nigeria has been rated as unsatisfactory, negatively impacting the ambitions of retirees. The broad view is that changes in a few macroeconomic variables, such as the foreign exchange rate, annual inflation rate, savings deposit rate, and GDP (income), must have played a role in this issue. As a result, the purpose of this study is to look at the impact of these variables on the pension contribution funds. The research was conducted in Nigeria, and annual data sets on pension contributions and other macroeconomic factors were acquired for the years 2004 through 2020. The long and short run dynamics of some macroeconomic variables and pension contribution were analyzed using the Auto-regressive Distributed Lag method. The analysis demonstrates a positive and significant association between exchange rate and pension contributions in both the long and short run. Similarly, inflation rate demonstrates a negative and statistically significant link with pension contributions in both the long and short run. The results also show that the Error Correction Model (ECM) coefficient has the correct sign: negative, less than one, and statistically significant which means that, the system will correct itself at a rate of 38 percent from the short to the long run. The study concludes that there should be concerted efforts by the government to curve the excessive inflation rate down, deposit rate should be monitored and always relate it to pensioners fund in order to maintain its financial sustainability.